2022
DOI: 10.3390/genes13122366
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on a Short-Time Treatment with the IL-4/IL-13 Receptor Blocker in Patients with CRSwNP: microRNAs Modulations and Preliminary Clinical Evidence

Abstract: Already used for the treatment of some allergic and inflammatory diseases, such as asthma or atopic dermatitis, dupilumab has also been approved as add-on therapy for patients with CRSwNP, and it could represent the keystone to reducing the remission time as well as to improve healing and quality of life. On the other hand, the role of miRNAs as potential biomarkers of immune modulation is emerging. We analyzed the effects of a short-time treatment with dupilumab in patients with CRSwNP, analyzing the immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Other pathways investigated or identified in these studies include those related to T cells and cytokines ( 40 , 43 , 48 , 55 , 60 , 66 ), eosinophil trafficking ( 59 ), PI3K/AKT signaling ( 40 , 56 , 58 , 65 , 75 ), Ras–MAPK signaling ( 47 , 66 , 69 , 75 ), Wnt signaling ( 47 , 57 ), ECM ( 83 , 84 ), adherens junctions ( 65 , 83 , 84 ), focal adhesions ( 47 , 65 , 84 ), matrix metalloproteinases ( 77 ), vascular permeability ( 45 , 78 ), cell cycle and apoptosis ( 64 , 85 ), EGF ( 74 ), ROR alpha (on exposure to pollution) ( 61 ), and IRF4 ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other pathways investigated or identified in these studies include those related to T cells and cytokines ( 40 , 43 , 48 , 55 , 60 , 66 ), eosinophil trafficking ( 59 ), PI3K/AKT signaling ( 40 , 56 , 58 , 65 , 75 ), Ras–MAPK signaling ( 47 , 66 , 69 , 75 ), Wnt signaling ( 47 , 57 ), ECM ( 83 , 84 ), adherens junctions ( 65 , 83 , 84 ), focal adhesions ( 47 , 65 , 84 ), matrix metalloproteinases ( 77 ), vascular permeability ( 45 , 78 ), cell cycle and apoptosis ( 64 , 85 ), EGF ( 74 ), ROR alpha (on exposure to pollution) ( 61 ), and IRF4 ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…These include involvement of the mucin type-O-glycan biosynthesis pathway ( 44 , 62 , 65 , 66 , 81 ), mucin secretion ( 76 ), and identification of GALNT7 through a lncRNA study ( 44 ). Impairment of pathways and implication of genes involved in structural integrity include COL18A1 ( 28 ), integrin genes ( ITGB2 , ITGAL , and ITGAM ) ( 31 ), KRT19 ( 26 ), alpha-SMA , fibronectin , and collagen type 1 ( 32 , 33 ), and miRNA studies have found pathways involving adherens junctions ( 65 , 83 , 84 ) and focal adhesions ( 47 , 65 , 84 ). An impaired epithelial barrier is a commonly accepted pathophysiological mechanism in CRS, and whether the epigenetic modifications in genes involved in the nasal epithelial structure is a cause or consequence of the inflammatory process is yet to be discerned.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the treatment, a decrease in the expression of miRNAs-25-3p and -185-5p was shown in the blood. As was proven, they are involved in the inflammatory process, T lymphocyte regulation, and drug resistance, thanks to which we note a significant clinical improvement among the subjects after using the drug [52]. Currently, no studies show the relationship between Dupilumab and miRNAs in asthmatics.…”
Section: Mirnas and Individual Groups Of Drugs Used In Asthma (Glucoc...mentioning
confidence: 59%
“…The inhibition of the IL-4/IL-13 axis by dupilumab should be recognized as a multisystemic effect ( 30 , 31 ). Our results showed the overall improvement of the clinical picture that dupilumab offers for patients with severe AD and persistent allergic asthma of any severity.…”
Section: Discussionmentioning
confidence: 99%